WEBVTT
00:00:02.200 --> 00:00:06.320
Find, in its simplest form, an expression for the determinant.
00:00:07.280 --> 00:00:10.960
Hereβs our three-by three-matrix.
00:00:11.720 --> 00:00:18.080
To find the determinate in this three-by-three matrix, weβll use the first row.
00:00:19.000 --> 00:00:41.000
The first row the first column will be positive, first row second column negative, and first row third column positive.
00:00:41.840 --> 00:00:47.480
To find the determinant, weβre gonna break this up into three smaller determinants.
00:00:48.480 --> 00:01:01.800
Starting with nine minus two π, we want to take this value and multiply it by the smaller matrix created by removing both the row and the column that nine minus two π is located in.
00:01:03.520 --> 00:01:10.400
Weβll multiply positive nine minus two π times the determinant of the two-by-two matrix created here.
00:01:11.000 --> 00:01:12.280
And this will be our first term.
00:01:13.120 --> 00:01:26.160
Our second term will be negative negative two π multiplied by the two-by-two matrix we create when we remove the row and the column that negative two π is found in.
00:01:27.040 --> 00:01:34.640
The two-by-two matrix would look like this: negative two π, seven π, negative two π, nine plus seven π.
00:01:35.040 --> 00:01:36.400
This will be our second term.
00:01:37.480 --> 00:01:53.200
Following in the same pattern, weβll take seven π and multiply it by the two-by-two matrix created when you remove the column and the row that seven π is located in, which will look like this and would be our third term.
00:01:54.800 --> 00:01:58.960
Now we have some major algebra to do.
00:01:59.440 --> 00:02:02.840
Iβm going to bring down the part that comprises the first term.
00:02:03.280 --> 00:02:06.040
And for now, weβll ignore the second and third term.
00:02:07.600 --> 00:02:16.000
Nine minus two π is what we start with, but remember we need the determinant of this two-by-two matrix.
00:02:16.840 --> 00:02:26.720
And that means multiplying negative one minus two π times nine plus seven π and then subtracting that value from seven π times negative two π.
00:02:27.640 --> 00:02:29.760
And all of this will solve for our first term.
00:02:30.760 --> 00:02:38.760
Looking inside the brackets, we need to multiply negative one minus two π times nine plus seven π.
00:02:39.960 --> 00:02:42.200
Negative one times nine is negative nine.
00:02:42.600 --> 00:02:45.280
Negative one times seven π, negative seven π.
00:02:46.160 --> 00:02:53.240
Moving to our negative two π, multiply that by nine, and we get negative 18π.
00:02:53.800 --> 00:02:58.280
Negative two π times seven π equals negative 14ππ.
00:02:59.120 --> 00:03:03.880
Still inside the brackets, we need to multiply seven π times negative two π.
00:03:04.280 --> 00:03:06.600
That equals negative 14ππ.
00:03:07.400 --> 00:03:08.960
And weβre dealing with subtraction.
00:03:09.440 --> 00:03:12.960
We know that subtracting a negative can be represented with addition.
00:03:13.600 --> 00:03:20.960
And now inside the brackets, we have negative 14ππ plus 14ππ.
00:03:21.480 --> 00:03:23.360
Those cancel out.
00:03:23.960 --> 00:03:29.920
The remaining portion of our brackets is negative nine minus seven π minus 18π.
00:03:30.400 --> 00:03:33.280
And we need to multiply this by nine minus two π.
00:03:34.240 --> 00:03:37.200
Nine times negative nine equals negative 81.
00:03:37.800 --> 00:03:41.840
Nine times negative seven π equals negative 63π.
00:03:42.400 --> 00:03:47.720
Nine times negative 18π equals negative 162π.
00:03:49.040 --> 00:03:55.760
And with our negative two π, negative two π times negative nine equals 18π.
00:03:56.760 --> 00:04:01.200
Negative two π times negative seven π equals positive 14ππ.
00:04:01.960 --> 00:04:08.840
And negative two π times negative 18π equals positive 36ππ.
00:04:09.560 --> 00:04:11.320
And this value is our first term.
00:04:13.120 --> 00:04:16.920
We need to follow the same process to find terms two and three.
00:04:17.960 --> 00:04:25.080
For term two, weβre dealing with negative negative two π, which we can write as positive two π.
00:04:26.040 --> 00:04:31.720
And we need to multiply two π by the determinant of this two- by-two matrix.
00:04:32.800 --> 00:04:41.800
That determinant is found by multiplying negative two π times nine plus seven π and then subtracting seven π times negative two π.
00:04:43.040 --> 00:04:48.160
Inside the brackets, negative two π times nine is negative 18π.
00:04:48.800 --> 00:04:52.800
Negative two π times seven π equals negative 14ππ.
00:04:53.920 --> 00:05:00.240
Weβre subtracting seven π times negative two π, negative 14ππ.
00:05:01.920 --> 00:05:04.320
Again, weβre subtracting a negative.
00:05:04.800 --> 00:05:06.800
We can make that more clear by making an addition.
00:05:07.400 --> 00:05:13.160
What we see now is negative 14ππ plus 14ππ inside the brackets.
00:05:13.840 --> 00:05:15.920
Adding those together, we get zero.
00:05:16.560 --> 00:05:20.000
Now we need to multiply negative 18π by two π.
00:05:20.560 --> 00:05:23.280
Weβre left with negative 36ππ.
00:05:23.680 --> 00:05:24.600
This is our second term.
00:05:26.280 --> 00:05:29.000
We have the same procedure one more time.
00:05:29.640 --> 00:05:34.400
Weβll put it here: seven π times the determinant of this two-by-two matrix.
00:05:35.560 --> 00:05:44.000
We find that by multiplying negative two π times negative two π and then subtracting negative one minus two π times negative two π.
00:05:44.480 --> 00:05:49.840
Moving inside the brackets, negative two π times negative two π equals four ππ.
00:05:50.560 --> 00:05:51.120
We are subtracting.
00:05:51.760 --> 00:05:55.840
Weβll distribute this negative two π over the negative one minus two π.
00:05:56.640 --> 00:05:59.240
Negative two π times negative one equals two π.
00:05:59.680 --> 00:06:03.960
Negative two π times negative two π equals positive four ππ.
00:06:05.600 --> 00:06:11.760
Now we need to distribute this negative sign to both the two π and the four ππ.
00:06:12.600 --> 00:06:17.240
And inside the brackets, weβll say four ππ minus two π minus four ππ.
00:06:18.360 --> 00:06:28.080
The four ππs cancel out, and we have seven π times negative two π, multiplied together, equals negative 14ππ, which is our third term.
00:06:29.520 --> 00:06:35.080
The next thing we need to do is add our first, second, and third terms together.
00:06:36.160 --> 00:06:38.400
Iβm gonna clear off some space to make room to do that.
00:06:39.280 --> 00:06:44.720
So if you wanna pause the video to copy any of this down, you can do that now.
00:06:47.200 --> 00:06:47.800
So here we go!
00:06:48.240 --> 00:06:51.960
Our first time plus our second term plus our third term.
00:06:52.960 --> 00:06:54.400
Do you notice anything here?
00:06:56.000 --> 00:07:19.880
When weβre adding, we have a positive 14ππ and a negative 14ππ; these will cancel out β as well, positive 36ππ and negative 36ππ β leaving us with negative 81 minus 63π minus 162π and 18π.
00:07:20.920 --> 00:07:26.320
We can simplify this a little bit further by noticing that all the constants are factors of nine.
00:07:27.320 --> 00:07:48.240
If we take out negative nine, divide negative 81 by negative nine, and you get nine, divide negative 63π by negative nine, and you get positive seven π, divide negative 162π by negative nine, and you get positive 18π.
00:07:49.040 --> 00:07:53.960
18π divided by negative nine equals negative two π.
00:07:54.960 --> 00:08:08.200
The simplified expression of this determinant, the simplified form of this determinant, is negative nine times nine plus seven π plus 18π minus two π.